The Assessment of Climate Risk Impact on the Economy: A Panel Data Approach - Teodora Cristina Barbu; Cosmin-Octavian Cepoi; Crina Raluca Petrescu; Mariana Vuță (Amfiteatru Economic)
In this paper, we investigate how climate risk impacts the sovereign risk, the stock market evolution, and the degree of competitiveness, starting from the macroeconomic and financial effects globally produced by climate change. Using both quantile and logistic regression and a sample of 22 countries, of which 16 EU members and 6 OECD members, during the 2008-2019 period, the results highlight a negative relationship between climate risks and the evolution of stock market capitalization as a percentage of GDP. Moreover, the climate risk leads to an increase in sovereign risk only across inferior quantiles, i.e., when the CDS level is small. In addition, based on a logit regression model, we show that the level of competitiveness of a country is influenced to a small extent by the level of climate risk. This could be a consequence of concerns among authorities and companies in each country willing to implement development strategies to achieve the goals proposed by the European Green Pact and standardization of the global price of CO2.